MicroRNAs as T Lymphocyte Regulators in Multiple Sclerosis - Wang, Lin; Liang, Yuanyuan (Frontiers in Molecular Neuroscience, 2022)
MicroRNA (miRNA) is a class of endogenous non-coding small RNA with regulatory activities, which generally regulates the expression of target genes at the post-transcriptional level. Multiple Sclerosis (MS) is thought to be an autoimmune-mediated chronic inflammatory demyelinating disease of the central nervous system (CNS) that typically affect young adults. T lymphocytes play an important role in the pathogenesis of MS, and studies have suggested that miRNAs are involved in regulating the proliferation, differentiation, and functional maintenance of T lymphocytes in MS. Dysregulated expression of miRNAs may lead to the differentiation balance and dysfunction of T lymphocytes, and they are thus involved in the occurrence and development of MS. In addition, some specific miRNAs, such as miR-155 and miR-326, may have potential diagnostic values for MS or be useful for discriminating subtypes of MS. Moreover, miRNAs may be a promising therapeutic strategy for MS by regulating T lymphocyte function. By summarizing the recent literature, we reviewed the involvement of T lymphocytes in the pathogenesis of MS, the role of miRNAs in the pathogenesis and disease progression of MS by regulating T lymphocytes, the possibility of differentially expressed miRNAs to function as biomarkers for MS diagnosis, and the therapeutic potential of miRNAs in MS by regulating T lymphocytes.